The Importance of Gender-Neutral Uniforms: A Study Based on the Perceptions of B.Ed. and M.Ed. Students - P. B., Gautham; M., Aswani (Darul Yasin Al Sys, 2025)
Persistent gender-based discrimination underscores the need to evaluate educational practices that foster inclusion. This study’s objective was to assess B.Ed. and M.Ed. students’ attitudes toward gender-neutral uniforms, their level of agreement with this trend, and perceived societal influence. A survey design was employed to elicit respondents’ views on gender-neutral teaching attire and its potential impacts. Key findings indicate that B.Ed. and M.Ed. students generally hold positive attitudes toward gender-neutral uniforms; most aspiring educators view such attire favorably and believe it can help cultivate a welcoming learning environment. The study concludes that support for gender-neutral uniforms is salient among future teachers. The contribution and implication are that these attitudes may facilitate the adoption of attire policies aligned with inclusive educational climates and inform discussions about the broader social acceptance of gender-neutral practices.